Peluang Ekonomi Rehabilitasi Tanaman Lada Menggunakan Tajar - Listyati, D. (Politeknik Negeri Lampung., 2010)
Pepper production and export in Indonesia, since last few years, tend to decrease because of various problems i.e: lack of maintenance, pests and diseases attack, old plant/ damaged, not using superior vareties with high productivity, and fluctuation of price. Opportunity of Indonesian pepper agribusiness in domestic and International market still high also opened for ? Lampung black pepper? and ? Muntok white pepper?. Looking the market opportunity and pepper problems, for the solution was coducted rehabilitate pepper plant, from pepper plant with hard damaged, old plant, low productivity also cannot be improved again so require to be changed with superior varieties which better potential production and resistance to pests and disease, and applying recommended cultivation. This research was conducted to know feasibility level of pepper plant rehabilitation using living post with investment feasibility criteria used Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit Cost Ratio (Net B/C ratio) and Payback period. Analisis result showed that pepper plant rehabilitation using living post feasible to conducted. Key word: Pepper, Economic opportunity, rehabilitation, living post